Probiotics potential of lactic acid bacteria from horse milk in Tambora, West Nusa Tenggara, Indonesia - Sulistiani,; Setiarto, R. Haryo Bimo; Dewi, Fera R.; Yusuf, Dandy; Fathoni, Ahmad; Handayani, Rini; Anggadhania, Lutfi; Anshory, Lutfi; Setianingrum, Ninu; Khusniati, Tatik (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study explores the probiotic potential of lactic acid bacteria (LAB) in horse milk from Tambora, West Nusa Tenggara by examining its functional and probiotic attributes, including bile salt tolerance, low pH, simulated gastric juice (SGJ), simulated intestinal juice (SIJ), antibacterial activity, as well as bile salt hydrolase (BSH) genes. Genotyping of LAB was performed using restriction fragment length polymorphism-polymerase chain reaction (RFLP-PCR) analysis and then identified based on the 16S rRNA gene. A total of 25 LAB isolates showed the ability to grow at low pH, tolerant to bile, and survived under SIJ and SGJ conditions. The BSH gene was confirmed in three isolates, namely: SK1-28, SK2-30, and SK2-34. Results of RFLP-PCR analysis showed that the LAB isolates were grouped into three groups based on the number and molecular weight of the differences DNA fragments. The 16S rRNA analysis showed that the first two groups were Lacticaseibacillus rhamnosus, whereas the third group was Lactiplantibacillus plantarum. In addition, all Lacticaseibacillus rhamnosus isolates in group I showed the ability to grow at pH 9.0, but not group II. It can be concluded that Lacticaseibacillus rhamnosus and Lactiplantibacillus plantarum can be used as the indigenous probiotic bacteria source from Indonesia.